Effects of Kefir as a Probiotic on Serum Cholesterol, Total Lipid, Aspartate Amino Transferase and Alanine Amino Transferase Activities in Broiler Chicks - Çenesiz, S.; Yaman, H.; Özcan, A.; Kart, A.; Yenice, G. (My University, 2008)
The effect of varied amounts of kefir applied in drinking water was investigated in relation to changes in total cholesterol serum, total lipid, aspartate amino transferase (AST) and alanine amino transferase (ALT) activities in broiler chicks. Ninety broiler chicks (one-day old) with an average weight of 37 g were divided into 3 groups including one control and 2 experimental groups. While all groups were fed with the same ration, they received kefir added in drinking water according to following regimen: chicks in the control group received normal drinking water ad libitum, group 1 was treated with 5% kefir in drinking water ad libitum and group 2 was given 7.5% kefir in drinking water ad libitum, respectively. At the end of experiment (42 day), live weights of the groups were as follows group 1: 2305 g, group 2: 2363 g and group 3: 2388 g. Live weights of chicks in group 3 significantly increased (p < 0.05) compared to that of the control group. Total cholesterol serum and total lipid levels were significantly reduced (p < 0.05) in groups 2 and 3 compared to that of in control group in response to kefir treatment. Moreover, kefir treatment in the groups did not result in any changes in serum AST and ALT activity. The obtained results demonstrate that use of kefir as a probiotic in drinking water increases live weight, lowers total cholesterol and total lipid thus suggesting that its use in human diets may have beneficial effects.
Keywords: Broiler Chicks; Kefir; Probiotic